Augustine's Doubts on Divorce: Reconsiderations on Remarriage - Hunter, David G. (Augustinian studies, 2017)
Augustine's teaching on the indissolubility of marriage profoundly influenced the Western Christian tradition on the matter of divorce and remarriage. Augustine famously insisted that while divorce was allowed in limited circumstances (e.g., on account of adultery by one of the spouses), remarriage was prohibited for both the guilty and the innocent parties. Less frequently acknowledged is the degree to which Augustine expressed doubt about the validity of his own teaching. In this essay I argue that even though Augustine offered a strict interpretation of the biblical evidence, he did so only tentatively and often expressed doubts about the adequacy of his own views. The reason for this hesitation, I suggest, was Augustine's knowledge that the meaning of the scriptural texts was ambiguous at best and that a significant portion of the previous tradition differed from the interpretation he favored.